2017
DOI: 10.1002/hep.29290
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cystatin C is a predictor of renal dysfunction, acute‐on‐chronic liver failure, and mortality in patients with acutely decompensated liver cirrhosis

Abstract: Baseline CysC is a biomarker of RD, HRS, and ACLF and an independent predictor of mortality in patients with acutely decompensated liver cirrhosis, though determining CysC at day 3 did not provide any benefit; while NGAL is also associated with short-term mortality, it fails to predict development of RD, HRS, and ACLF. Baseline CysC may help to identify patients at risk earlier and improve clinical management. (Hepatology 2017;66:1232-1241).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 41 publications
8
81
4
1
Order By: Relevance
“…Not surprisingly, renal dysfunction and coagulation dysfunction seem to be highly associated with the development of ACLF after surgery in patients with Child‐Pugh grade A. This is in line with previous findings, which attribute a special role to renal and coagulation function in the development of ACLF …”
Section: Discussionsupporting
confidence: 91%
“…Not surprisingly, renal dysfunction and coagulation dysfunction seem to be highly associated with the development of ACLF after surgery in patients with Child‐Pugh grade A. This is in line with previous findings, which attribute a special role to renal and coagulation function in the development of ACLF …”
Section: Discussionsupporting
confidence: 91%
“…CysC was also a predictor for predicting the development of ACLF. Recently, Markwardt et al [80] measured the plasma levels of CysC in 429 patients hospitalized for acutely decompensated cirrhosis and results showed that the baseline CysC level was not only a predictor of renal dysfunction (OR: 9.4) but also a predictor of HRS, ACLF, and 90-day mortality (OR: 4.2, 5.9, and 3.1, respectively). Maiwall et al [81] developed AKI-Score including bilirubin, Cystatin C, and prior AKI to predict the new AKI in patients with LC.…”
Section: Predicting the Renal Injurymentioning
confidence: 99%
“…Neuere Untersuchungen weisen darauf hin, dass die Bestimmung von Cystatin C im Blut und Urin sowohl als aussagekräftiger Prädiktor für HRS-AKI, Non-HRS-AKI, ACLF und Mortalität als auch zur Differenzierung zwischen einer akuten Tubulusnekrose und einem HRS-AKI verwendet werden kann [81][82][83]. Die lokal eingeschränkte Verfügbarkeit und die hohen Kosten des Reagens haben bislang eine breite Anwendung in der klinischen Praxis nicht erlaubt.…”
Section: Serumkreatinin Gfr Harnstoff Und Cystatin C Als Marker Derunclassified